MFN2 Deficiency Impairs Mitochondrial Functions and PPAR Pathway During Spermatogenesis and Meiosis in Mice - Wang, Tianren; Xiao, Yuan; Hu, Zhe; Gu, Jingkai; Hua, Renwu; Hai, Zhuo; Chen, Xueli; Zhang, Jian V.; Yu, Zhiying; Wu, Ting; Yeung, William S. B.; Liu, Kui; et al. (Frontiers in Cell and Developmental Biology, 2022)
Mitochondria are highly dynamic organelles and their activity is known to be regulated by changes in morphology via fusion and fission events. However, the role of mitochondrial dynamics on cellular differentiation remains largely unknown. Here, we explored the molecular mechanism of mitochondrial fusion during spermatogenesis by generating an Mfn2 (mitofusin 2) conditional knock-out (cKO) mouse model. We found that depletion of MFN2 in male germ cells led to disrupted spermatogenesis and meiosis during which the majority of Mfn2 cKO spermatocytes did not develop to the pachytene stage. We showed that in these Mfn2 cKO spermatocytes, oxidative phosphorylation in the mitochondria was affected. In addition, RNA-Seq analysis showed that there was a significantly altered transcriptome profile in the Mfn2 deficient pachytene (or pachytene-like) spermatocytes, with a total of 262 genes up-regulated and 728 genes down-regulated, compared with wild-type (control) mice. Pathway enrichment analysis indicated that the peroxisome proliferator-activated receptor (PPAR) pathway was altered, and subsequent more detailed analysis showed that the expression of PPAR α and PPAR γ was up-regulated and down-regulated, respectively, in the MFN2 deficient pachytene (or pachytene-like) spermatocytes. We also demonstrated that there were more lipid droplets in the Mfn2 cKO cells than in the control cells. In conclusion, our study demonstrates a novel finding that MFN2 deficiency negatively affects mitochondrial functions and alters PPAR pathway together with lipid metabolism during spermatogenesis and meiosis.